Impact of Chemical Analogs of 4-Hydroxybenzoic Acid on Coenzyme Q Biosynthesis: From Inhibition to Bypass of Coenzyme Q Deficiency - Pierrel, Fabien (Frontiers in Physiology, 2017)
Coenzyme Q is a lipid that participates to important physiological functions. Coenzyme Q is synthesized in multiple steps from the precursor 4-hydroxybenzoic acid. Mutations in enzymes that catalyze reactions of coenzyme Q biosynthesis result in primary coenzyme Q deficiency, a type of mitochondrial disease. Coenzyme Q10 supplementation of patients is the classical treatment but it shows limited efficacy in some cases. The molecular understanding of the coenzyme Q biosynthetic pathway allowed the design of experiments to bypass deficient biosynthetic steps with analogs of 4-hydroxybenzoic acid. These molecules provide the defective chemical group and can reactivate endogenous coenzyme Q biosynthesis as demonstrated recently in yeast, mammalian cell cultures and mouse models of primary coenzyme Q deficiency. This mini review presents how the chemical properties of various analogs of 4-hydroxybenzoic acid dictate the effect of the molecules on CoQ biosynthesis and how the reactivation of endogenous coenzyme Q biosynthesis may achieve better results than exogenous CoQ10 supplementation.